Yufid Kids Cartoon Media Effectiveness in Learning Arabic For Early Children - Chusniah Risnawati; Imam Asrori; M. Abdul Hamid (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
Education is one of the most important aspects in the formation of the development of human life. In practice there are many learning methods that can be used in conveying messages to a student, and one of the methods used in the process of educational development in early childhood is to using the animation media method, where in the learning process students also involve various additional media elements in it, animation learning media is a means of conveying information from the sender of the message to the recipient of the message, in the hope that the learning communication process can run effectively and the message is want to be conveyed can be accepted completely by children so that in the end it will improve children's language skills by involving elements of images and sounds. Where in this learning takes place and can attract the attention of students both in learning activeness, asking questions, and interacting. This can be seen from the positive attitudes of students seen during the learning process. This study uses a qualitative method approach by examining several literature studies related to the research objectives, namely to find out how to apply learning methods using cartoon animation media in improving Arabic for early childhood.